Bibliometric analysis and visualization of lipid droplets in the central nervous system: research hotspots and Frontiers (2000–2024) - Wang, Yanan; Chen, Simin; Lv, Xinyi; He, Jiahui; Liang, Xiao; Song, Yuehan (Frontiers in Aging Neuroscience, 2025)
ObjectiveThe aim of this study is to conduct bibliometric analysis and visualization of the research progress of lipid droplets in the central nervous system in detail using CiteSpace, VOSviewer, and to explore the current research status, hotspots, and research trends, with a view to providing a basis for future research.MethodsThis study utilized the Web of Science database to search for 1,066 relevant publications on lipid droplets in the central nervous system from 2000 to 2024. Bibliometric analysis was conducted using CiteSpace and VOSviewer software, producing metrics such as annual publication trends, contributions by countries, institutions, and authors, keyword co-occurrences, and reference co-citation networks. The literature of 25 years or so was explored visually to identify the important areas of lipid droplets in neurological research.ResultsMiguel Lopez is the largest contributor to the relevant literature with 10 publications. The United States, China, Johns Hopkins University, the University of Cambridge, and Zhejiang University are the top contributors in terms of publication volume in this research area. Current research emphasizes the mechanisms of lipid droplets in oxidative stress, neuroinflammation, and related degenerative diseases, with a particular focus on Alzheimer's Disease.ConclusionOur analysis suggests enhancing collaboration among countries, institutions, and authors in clinical and basic research on brain lipid droplets.